Feminist Stylistic Analysis of Ava Maxâ€™s Song â€œNot Your Barbie Girlâ€ - Manurung, Anna Shinta Vholyna; Perangin-angin, Angelia Maria Igesia; Tanjung, Putri Aziza Muvta; Hasanah, Nurul; Marsha, Siti Azzahra; Rangkuti, Rahmadsyah (Fakultas Ilmu Budaya, Universitas Jambi, 2023)
This study analyzes Ava Max's